2001
DOI: 10.1093/emboj/20.22.6404
|View full text |Cite
|
Sign up to set email alerts
|

hADA3 is required for p53 activity

Abstract: The tumor suppressor protein p53 is a transcription factor that is frequently mutated in human cancers. In response to DNA damage, p53 protein is stabilized and activated by post‐translational modifications that enable it to induce either apoptosis or cell cycle arrest. Using a novel yeast p53 dissociator assay, we identify hADA3, a part of histone acetyltransferase complexes, as an important cofactor for p53 activity. p53 and hADA3 physically interact in human cells. This interaction is enhanced dramatically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
87
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 45 publications
(105 reference statements)
10
87
0
1
Order By: Relevance
“…hAda3 regulates p300-mediated p53 acetylation The hAda3 protein complexes with both p53 and p300 and enhances p53 transcriptional activity (Wang et al, 2001;Kumar et al, 2002). We confirmed hAda3 binding to p53 by coimmunoprecipitation of Flag-hAda3 and p53 following transfection into p53 null human H1299 cells.…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…hAda3 regulates p300-mediated p53 acetylation The hAda3 protein complexes with both p53 and p300 and enhances p53 transcriptional activity (Wang et al, 2001;Kumar et al, 2002). We confirmed hAda3 binding to p53 by coimmunoprecipitation of Flag-hAda3 and p53 following transfection into p53 null human H1299 cells.…”
Section: Resultssupporting
confidence: 59%
“…We confirmed hAda3 binding to p53 by coimmunoprecipitation of Flag-hAda3 and p53 following transfection into p53 null human H1299 cells. While chemical cross-linking was previously required to detect their association (Wang et al, 2001), this step was not necessary in our experiments (Supplementary Information Figure 1). Interestingly, inclusion of HDM2 did not reduce Flag-hAda3 coimmunoprecipitation with p53.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies of ADA2a and ADA2b in higher eukaryotes, including mammals, have demonstrated that these proteins assemble into multiple complexes that vary considerably. In addition, hADA3 also participates in these complexes and associates with p53; hADA3 overexpression increases the transcriptional activity of p53 by affecting p53 acetylation [25][26][27].…”
Section: Discussionmentioning
confidence: 99%